2022
DOI: 10.1136/bjophthalmol-2021-320842
|View full text |Cite
|
Sign up to set email alerts
|

Lens capsule-related complications in femtosecond laser-assisted cataract surgery: a study based on video analysis

Abstract: PurposeTo analyse the occurrence and potential causes of lens capsule-related complications during femtosecond laser-assisted cataract surgery (FLACS).MethodsThis prospective consecutive cohort study included the first 1600 eyes (from 1140 consecutive patients) who received FLACS performed by the same surgeon from May 2015 to December 2018. The potential causes and characteristic signs of capsulotomy-related complications, including incomplete capsulotomies and radial anterior capsule (AC) tears, were summaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Other studies also showed the presence of a steep learning curve in the initial 100 to 200 FLACS cases, with an increased risk of complications, including incomplete capsulotomy. 90,91 However, stabilization of complication rates was observed after 200 FLACS cases. 90,91 Of note, FLACS may require additional time and effort for both surgeons and patients because it is associated with an increased duration of cataract surgery, and it requires the transport of the patients or microscope during surgery.…”
Section: Complications and Limitations Of Flacsmentioning
confidence: 97%
See 4 more Smart Citations
“…Other studies also showed the presence of a steep learning curve in the initial 100 to 200 FLACS cases, with an increased risk of complications, including incomplete capsulotomy. 90,91 However, stabilization of complication rates was observed after 200 FLACS cases. 90,91 Of note, FLACS may require additional time and effort for both surgeons and patients because it is associated with an increased duration of cataract surgery, and it requires the transport of the patients or microscope during surgery.…”
Section: Complications and Limitations Of Flacsmentioning
confidence: 97%
“…90,91 However, stabilization of complication rates was observed after 200 FLACS cases. 90,91 Of note, FLACS may require additional time and effort for both surgeons and patients because it is associated with an increased duration of cataract surgery, and it requires the transport of the patients or microscope during surgery. As there is still a controversy regarding the superiority in the visual and refractive outcomes of FLACS, 5,[36][37][38][39] expert cataract surgeons may not choose to use FLACS for general cataract cases.…”
Section: Complications and Limitations Of Flacsmentioning
confidence: 97%
See 3 more Smart Citations